Towards Extraction of Massive DIB Datasets from Stellar Spectroscopic Surveys. Issue Volume 9:Issue S297(2013) (21st February 2014) - Lallement, R.; Chen, H.C; Puspitarini, L.; Bonifacio, P.; Babusiaux, C.; Hill, V.
Abstract: Medium to high-resolution stellar spectroscopic surveys can potentially be used to build DIB databases by means of automated methods of analysis. Multiplex spectrographs increase strongly those potentialities and allow small-scale variability studies. Because measurements of the stellar parameters are generally the primary goal of the surveys, synthetic spectra can be computed and used to extract DIBs from late-type star data. Large datasets should allow deeper investigations on the DIB variability in response to stellar radiation fields, DIB reddening relationships, and help localizing interstellar clouds. Here we describe our attempts to build and test automated methods adapted to both early and late type stars.